Labour and the Popular Welfare - Mallock, W. H. (William Hurrell), 1849-1923 (Salt Lake City, UT : Project Gutenberg, 2021)
"Labour and the Popular Welfare" by W. H. Mallock is a critical examination of economic and social issues, likely written in the late 19th century. This work engages with the concepts of wealth distribution, the economic roles of different social classes, and the implications of proposed social reforms. The author aims to present arguments that resonate with both Radicals and Conservatives, focusing on the centrality of personal income to national welfare and happiness. The opening portion of the book introduces the author's intent to address the pressing social issues of the time, particularly the labour question and wealth distribution, while maintaining a neutral stance free from party biases. Mallock emphasizes the importance of income as a foundation for personal and national well-being, arguing against the misconceptions surrounding the economic realities faced by various classes. He sets the stage for a detailed analysis by outlining the significance of understanding truths that underlie social and economic debates, aiming to educate voters about realistic perspectives on wealth and income distribution. (This is an automatically generated summary.)
Release date is 2021-10-11
Chris Curnow, Quentin Campbell, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Socialism; Working class; Labor; Labor movement